Long-term safety and tolerability of open-label aripiprazole augmentation of antidepressant therapy in major depressive disorder - Berman R (Dove Medical Press, 2011)
Robert M Berman1, Michael E Thase2, Madhukar H Trivedi3, James A Hazel4, Sabrina Vogel Marler5, Robert D McQuade6, William Carson7, Ross A Baker8, Ronald N Marcus91Neuroscience Global Clinical Research Bristol-Myers Squibb, Wallingford, CT, USA; 2Department of Psychiatry, University of Pennsylvania School of Medicine, Philadelphia, PA, USA; 3Division of Mood Disorders Research Program and Clinic, University of Texas Southwestern Medical School, Dallas, TX, USA; 4Neuroscience Global Clinical Research, Bristol-Myers Squibb, Wallingford, CT, USA; 5Global Biometric Sciences, Bristol-Myers Squibb, Wallingford, CT, USA; 6Global Medical Affairs at Otsuka Pharmaceutical Development & Commercialization, Inc., Princeton, NJ, USA; 7Global Clinical Development, Otsuka Pharmaceutical Development and Commercialization Inc, Princeton, NJ, USA; 8Neuroscience Medical Strategy, Bristol-Myers Squibb Company, Plainsboro, NJ, USA; 9Neuroscience Global Clinical Research, Bristol-Myers Squibb, Wallingford, CT, USABackground: Effective management of major depressive disorder often includes the long-term use of multiple medications, and the longer-term utility and safety of adjunctive aripiprazole has not been evaluated in a controlled setting.Patients and methods: Patients (n = 706) completing one of two 14-week double-blind studies of aripiprazole augmentation, as well as de novo patients (n = 296) nonresponsive to current antidepressant therapy, were enrolled in this open-label study. Patients received open-label aripiprazole for up to 52 weeks.Results: Open-label treatment was completed by 323 patients (32.2%). At endpoint (n = 987), the mean dose of aripiprazole was 10.1 mg/day. Common (>15% of patients) spontaneously reported adverse events were akathisia (26.2%), fatigue (18.0%), and weight gain (17.1%). The incidence of serious adverse events was 4.0%. Four spontaneous reports of possible tardive dyskinesia were submitted (0.4%); all resolved within 45 days of drug discontinuation. Mean weight change was 4.4 kg; 36.6% experienced ≥7% increase in weight from baseline (observed case analysis, n = 303). No clinically relevant changes in other metabolic parameters were seen. At the end of open-label treatment, 221 patients (69.7%) had a Clinical Global Impression-Severity of Illness score of 1 (not at all ill) or 2 (borderline ill).Conclusion: Long-term adjunctive aripiprazole therapy was well tolerated with an acceptable long-term safety and tolerability profile in patients with major depressive disorder who had not responded to treatment with one or more antidepressant therapies. Clinically significant weight gain was observed in about one-third of patients. Overall, the adverse event profile was consistent with that reported in the short-term trials and readily managed clinically.Keywords: adjunctive aripiprazole, antidepressant therapy, major depressive disorder, long-term safety and tolerability